The evolution of nervous system centralization - Arendt, Detlev (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2008)
It is yet unknown when and in what form the central nervous system in Bilateria first came into place and how it further evolved in the different bilaterian phyla. To find out, a series of recent molecular studies have compared neurodevelopment in slow-evolving deuterostome and protostome invertebrates, such as the enteropneust hemichordate Saccoglossus and the polychaete annelid Platynereis. These studies focus on the spatially different activation and, when accessible, function of genes that set up the molecular anatomy of the neuroectoderm and specify neuron types that emerge from distinct molecular coordinates. Complex similarities are detected, which reveal aspects of neurodevelopment that most likely occurred already in a similar manner in the last common ancestor of the bilaterians, Urbilateria. This way, different aspects of the molecular architecture of the urbilaterian nervous system are reconstructed and yield insight into the degree of centralization that was in place in the bilaterian ancestors.